Pengembangan E-Modul Interaktif Menggunakan Adobe Animate CC Pada Materi Ikatan Kimia dan Bentuk Molekul SMA/MA Sederajat - jamal hasibuan, Lusiana (Universitas Sulawesi Barat, 2023)
This research aims to develop an interactive e-module using the Adobe Animate Creative Cloud (CC) application on chemical bonds and molecular shapes that are valid and suitable for use in the learning process. This research is a qualitative descriptive study using the research design and development of the ADDIE model. Data collection techniques were carried out through library research and field studies, with data collection instruments using validation sheets and user response questionnaires. The research subjects consisted of 3 chemistry teachers and 26 students of class X SMA Negeri 2 Tambang and MAN 2 Pekanbaru City. The results and conclusions of this study are that the e-module developed is valid and feasible to use according to material validators and media validators with percentages of 98.83% and 97.20%, respectively. The results of the teacher response assessment get a score of 91.70% and the assessment by students gets a score of 96.01% with very good assessment criteria and can be used in the learning process. The conclusions of this study provide recommendations for further research related to the effectiveness of the use of e-modules when used in the learning process so that the developed e-modules prove to be effective for use during learning.